Environmental effect of boarding schools and SQ (spiritual quotient) toward learning outcomes physics - Ahlul Fikri Ramdhan; Wahyu Dian Laksanawati; Acep Kusdiwelirawan (Gravity: Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2020)
This study aimed to determine the correlation between boarding schools and spiritual quotient (SQ) on learning outcomes. The method used was a survey with quantitative approach, because there are two independent variables, then use path design analysis. The results obtained, the first, there was a significant relationship between the pesantren with the student learning outcomes, tcount = 2,22 > ttable(0,05)=1,69, a contribution of the boarding school environment to learning outcomes was 36.1% with the category enough. The second, there was a significant relationship between spiritual quotient with a physics student learning outcomes, tcount = 4,3 > ttable(0,05) = 1,69, a contribution spiritual abilities physics quotient on learning outcomes by 36% with the category enough. The third, there was a significant relationship between the pesantren and spiritual quotient on learning outcomes tcount  ≥ ttable(0,05)=1,69.